The Influence of self-efficacy, work discipline, and compensation on employee performance through work motivation in textile and garment companies in West Java - Sjarifudin, Didin; Widyastuti, Tri; Renwarin, Joseph MJ; Suroso, Sugeng (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to examine the influence of self-efficacy, work discipline, and compensation on employee performance through work motivation in textile and garment companies in West Java. Methodology/approach: The method used in this study is descriptive quantitative. The population in this study is unknown, with a sample size of 370 respondents. The data used in this study are primary and secondary. The analytical tools used in this study include SmartPLS. The tests conducted in this study include Validity Test, Reliability Test, Inner Model, Outer Model, and Hypothesis Testing. Results/findings: The results of the study conducted on Textile and Garment Companies in West Java are as follows: 1) Self-efficacy has a positive and significant effect on motivation; 2) Work discipline has no effect and is not significant on motivation; 3) Compensation has no effect and is not significant on motivation; 4) Self-efficacy has a positive and significant effect on employee performance; 5) Work discipline has a positive and significant effect on employee performance; 6) Compensation has a positive and significant effect on employee performance; 7) Motivation has a positive and significant effect on employee performance; 8) Self-efficacy has a positive and significant effect on employee performance through motivation; 9) Work discipline does not have a positive and significant effect on employee performance through motivation; and 10) Compensation does not have a positive and significant effect on employee performance through motivation. Conclusions: The study concludes that self-efficacy significantly enhances both work motivation and employee performance, with motivation acting as a mediating factor. Work discipline directly improves performance but does not significantly affect motivation. Compensation shows no significant effect on either motivation or performance. Work motivation itself has a strong positive impact on performance. Indirectly, only self-efficacy improves performance via motivation, while work discipline and compensation do not demonstrate such mediation.. Limitations: This study is limited to Employee Performance and Work Motivation. Contribution: This study contributes to the understanding of factors that influence employee performance, focusing on factors such as self-efficacy, work discipline, compensation, and work motivation.